Multicast Energy Aware Routing in Wireless Networks - Ahmad Karimi (Universitas Sriwijaya, 2016)
Multicasting is a service for disseminating data to a group of hostsand it is of paramount importance in applications with a close collabo-ration of network hosts. Due to limited energy available in the wirelessdevices, energy management is one of the most important problems inwireless networks. Energy aware routing strategies help us to mini-mize the energy costs for communication as much as possible and toincrease the network lifetime. In this paper, we address the problemof energy efficient routing to increase the lifetime of the network. Wepresent three new strategies for online multicast energy aware routingin wireless networks to increase the network lifetime.